Antecedents of Viewers Engagement - Parningotan Sihaloho, Martua; Kurniawati, Kurniawati (Asian Journal of Social and Humanities, 2024)
The purpose of this study is to analyze the antecedents of viewers engagement from social media influencers specifically in relation to YouTube channels, which include feelings of escape, self-improvement, fun, glamourous, connectivity from the audience as well as Overall Perceived image of the influencer. The sample design used in this research is non-probability sampling with purposive sampling technique. The processed data came from 280 respondents and then the data was analyzed using the Structural Equation Modeling (SEM) method. The results of this study indicate that there is a positive influence of escape on fun, there is a positive influence of self improvement on fun, glamorous and connectivity, there is also a positive influence of fun, glamorous and connectivity on overall perceived image and there is a positive influence of overall perceived image on viewers engagement. Likewise, this study found that there is no positive effect of escape on glamorous and connectivity. In general, the results of this study show that fun, glamorous and connectivity, and overall perceived image are important factors that influence viewers engagement. Content that has a positive, authentic and informative overall image tends to attract more attention and is easily understood by viewers. Suggestions for future research, researchers can conduct research on Indonesian youtuber objects that are not included in this study and overseas youtuber objects. and can also conduct research on the impact of escape and self improvement on viewers engagement by adding job occupation variables as moderators.